Bulk superinsulation and polar nematic orders in nanopatterned NbTiN - A. Yu. Mironov; C. A. Trugenberger; M. C. Diamantini; D. A. Nasimov; V. M. Vinokur (Nature Communications)
Abstract We present experimental evidence of 3D superinsulation in a nanopatterned slab of NbTiN, given by the Vogel–Fulcher–Tamman (VFT) scaling of the conductance when approaching the critical temperature from above and by the vanishing of the conductance below the transition. In the electric Meissner state, we find polar nematic order arising from ferroelectric alignment of short electric strings excited by external electromagnetic fields. Our results prove that superinsulation appears also in ordered structures provided that these are large enough, thereby confirming the origin of superinsulation as electric confinement, independent of disorder.